Extracellular vesicle miRNAs in breast milk of obese mothers - Cho, Young Eun; Vorn, Rany; Chimenti, Michael; Crouch, Keith; Shaoshuai, Chen; Narayanaswamy, Janhavi; Harken, Alaria; Schmidt, Reegan; Gill, Jessica; Lee, Hyangkyu (Frontiers in Nutrition, 2022)
Background Breast milk has abundant extracellular vesicles (EVs) containing various biological molecules (cargo), including miRNAs. EVs are not degraded in the gastrointestinal system and circulation; thus, breast milk EVs (bEVs) are expected to interact with other organs in breastfed infants and modify the gene expression of recipient cells using miRNAs. Maternal pre-pregnancy BMI is a critical factor influencing the composition of breast milk. Thus, in mothers with obesity, miRNAs in bEVs can be altered, which might be associated with adverse health outcomes in infants. In this study, we examined 798 miRNAs to determine which miRNAs are altered in the bEVs of mothers with obesity and their potential impact on breastfed infants. Methods We recruited healthy nursing mothers who were either of normal weight (BMI < 25) or with obesity (BMI ≥ 30) based on their pre-pregnancy BMI, and delivered a singleton baby in the prior 6 months. EVs were isolated from breast milk with ultracentrifugation. bEV characteristics were examined by flow cytometry and fluorescence imaging of EV markers. A total of 798 miRNAs were screened using a NanoString human miRNA panel to find differentially expressed miRNAs in bEVs of mothers with obesity compared to mothers of normal weight. Results We included 65 nursing mothers: 47 of normal weight and 18 with obesity based on pre-pregnancy BMI. After bEV isolation, we confirmed the expression of various EV markers. Out of 37 EV markers, CD326 (EpCaM) was the most highly expressed in bEVs. The most abundant miRNAs in bEVs include miR-30b-5p, miR-4454, miR-494-3p, and let-7 miRNAs. Target genes of the top 10 miRNAs were associated with cancer, prolactin pathway, EGFR, ErbB, and FoxO signaling pathway. In bEVs of mothers with obesity, 19 miRNAs were differentially expressed (adjusted p < 0.05 cut-off), which include miR-575, miR-630, miR-642a-3p, and miR-652-5p. These miRNAs and their target genes were associated with neurological diseases and psychological disorders. Conclusion In this study, we characterized bEVs and demonstrated altered miRNAs in bEVs of mothers with obesity and identified the pathways of their potential target genes. Our findings will provide insight for future studies investigating the role of bEVs in breastfed infants.